Global Dynamics of an SIRSI Epidemic Model with Discrete Delay and General Incidence Rate - Bernoussi, Amine; Hattaf, Khalid (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we propose the global dynamics of an SIRSI epidemic model with discrete latent period and general nonlinear incidence function. By analyzing the corresponding characteristic equations, the local stability of the endemic equilibrium is established. By using suitable Lyapunov functionals and LaSalle's invariance principle, the global stability of the disease-free equilibrium and the endemic equilibrium are established for the SIRSI epidemic model with discrete latent period.